terraXcube: A new hi-tech training facility for EMS teams - Brugger, H.; Brodmann, M.; Turner, R.; Nollo, A.; Gatterer, H.; Strapazzon, G. (Resuscitation, 2018)
Purpose of the study: Training of emergency medical services (EMS) teams in mountain rescue focuses mainly on proficiency in technical or medical skills as independent components. However, the quality of resuscitation manoeuvres rapidly declines at high altitude and other manual tasks can be slowed by cold temperatures and other environmental factors. In order to lessen the decline and to improve the performance of EMS teams, a new facility has been realised.